(untitled) (Web of Technology: Multidimensional Research Journal, 2024)
This article discusses the impact of digital technologies on teacher-student activities in educational processes. The author provides an analysis of the main advantages of the digital environment, such as expanding the boundaries of education, individualizing education and developing communication skills. It also discusses the opportunities that the digital environment presents for future teachers and calls for the development of digital literacy and competencies in education. The article emphasizes the importance of using digital technologies to improve the quality of education and to adapt educational fields to modern requirements.